Major liver resection by a hanging maneuver for an infant with hepatoblastoma - Kobayashi, Megumi (International Scientific Literature, Inc., 2012)
BACKGROUND: The liver hanging maneuver (LHM) was reported to be a safe and accurate method for hepatectomy, and its use in adults has been increasing in recent years. Because fragility of a blood vessel and the tissue is concerned about in the children as compared with adults, the adaptation to children is subobsolete. CASE REPORT: We describe a case involving an extended right hepatic lobectomy using the LHM in a 5-month-old infant. We received LHM using foceps of the size identical to adults. There were no postoperative complications. CONCLUSIONS: Anterior approach is suitable for the hepatoblastomas to form a bulky tumor. LHM is a useful and safe technique for hepatectomy in pediatric surgery.